2016
DOI: 10.18632/oncotarget.6890
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stem-like cells and clinical significance of candidate stem cell markers in gastric cancer

Abstract: The existence of gastric cancer stem cells (CSCs) has not been definitively proven and specific cell surface markers for identifying gastric CSCs have largely not been identified. Our research aimed to isolate potential gastric CSCs and clarify their clinical significance, while defining markers for GCSC identification and verification. Here, we report that spheroid cells possess stem cell-like properties, and overexpress certain stem cell markers. CD133 or CD44-positive cells also exhibit properties of CSCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 52 publications
9
80
0
1
Order By: Relevance
“…Consistent with our previous data [22] we found that Ad-Bmi-1i can downregulate phosphorylated-AKT (pAKT). Besides this, Bmi-1 downregulation also leads to downregulation of pmTOR and reduction of VEGF in SGC-7901 cells (Figure 5A).…”
Section: Resultssupporting
confidence: 93%
“…Consistent with our previous data [22] we found that Ad-Bmi-1i can downregulate phosphorylated-AKT (pAKT). Besides this, Bmi-1 downregulation also leads to downregulation of pmTOR and reduction of VEGF in SGC-7901 cells (Figure 5A).…”
Section: Resultssupporting
confidence: 93%
“…Previously, the Akt and Erk signaling pathways were shown to be essential for maintaining the pluripotency of stem cells [23, 24]. Moreover, gastric spheroid cells are known to overexpress multiple stem cell markers, including Oct4, Sox2, Gli1, CD44, CD133, pAkt, and pErk [22]. Taken together, these results suggest that the phosphorylation of Akt and Erk by IQGAP3 is involved in spheroid formation by GC cells.…”
Section: Discussionmentioning
confidence: 60%
“…CSCs are defined as a unique subpopulation of cells that possess self-renewal and differentiation potential, and that are generally responsible for tumor initiation, invasion, metastasis, and chemo-resistance [22]. Thus, CSC characterization can improve our understanding of carcinogenesis and help explain the frequency of treatment failure for GC.…”
Section: Discussionmentioning
confidence: 99%
“…The protein is not only involved in cell-cell adhesion, cell-matrix interactions, and tumor survival, but also has been accepted as a CSC marker for gastric cancer in many studies[9]. CD44 expression is upregulated in advanced gastric lesions[10]. Depletion of CD44 inhibited the stem cell-like properties, which was accompanied by the downregulation of Oct4[10].…”
Section: Introductionmentioning
confidence: 99%